(3E)-3-[4-(Dimethylamino)phenyl]-1-(4-hydroxyphenyl)prop-2-en-1-one - Hasan, A.; Akhtar, N.; Lajis, N.; Rusli, A.F.; Lo, K.M. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(17)H(17)NO(2), contains two crystallographically independent molecules. Both molecules adopt a trans configuration about the C=C bond, with the C-C=C-C fragments in the two molecules twisted in opposite directions [torsion angles of 174.2 (2) and -175.8 (2)degrees]. The two benzene rings in each of the molecules make dihedral angles of 20.21 (6) and 48.64 (4)degrees. In the crystal, adjacent molecules are linked by O-H center dot center dot center dot O hydrogen bonds into infinite polymeric chains.